Learning Reflections to Build Learner Autonomy - Karpin Karpin; Ai Mahmudatussa'adah (INVOTEC, 2022)
The research objective was to improve the students' competency mastery which is the demand for lectures; building student learner autonomy; describes the stages of learning reflection to build learner autonomy. Quasi-experimental research is used to achieve research objectives. The research subject is a reflection of learning in the Statistics subject in the Culinary Education Study Program, Universitas Pendidikan Indonesia. This research used exit tickets and test instruments. The results of the study obtained an increase in student learning outcomes from the tests given; learner autonomy indicators are found in students' answers to exit tickets. The stages of learning reflection are first, the action taken as an experience (action); second, looking back on the actions that have been taken (looking back on the action); third, assessing the quality of decisions in real situations and overcoming limitations (awareness of essential aspects); fourth, making decisions for corrective actions (creating alternative methods of action); fifth, to continue the learning process with better action (trial). The conclusion of this research is that learning reflection can increase the mastery of student competence, build student learner autonomy, and there are five stages of learning reflection to build learner autonomy.